Transduction of p27 to induce apoptosis in tumor cells - Grdiša, Mira (Array, 2008)
Summary: Transduction is a biochemical technique for the introduction of full-length proteins into the cells. It has the potential to be used in the development of a new therapeutic strategy for cancer therapy. Different forms of p27 (TAT-p27, TAT-Mp27, TAT-p23) were transduced into tumor cell lines, lymphocytes and B-CLL cells, and their influence on proliferation and apoptosis was investigated. The metabolism of transduced proteins differed between the cell types. TAT-p27 protein is metabolized faster than the mutated form. Furthermore, the half-life of TAT-p27 depended on the type of cells. All forms of TAT-p27 fusion protein moderately decreased the proliferation of different types of the cells and induced apoptosis. The cells from some B-CLL patients were sensitive to TAT fusion proteins, and the sensitivity was increased with the addition of Fluda. This study provides valuable results for further development of TAT technology as the potential tool for a specially targeted therapy of tumors